Ball bouncing exercise - Nandi, J.K. (2007)
This exercise is aimed at demonstrating such dynamics that influence the individuals to achieve the organizational goal as a whole, more effectively and efficiently. During this exercise two balls (one small and the other big) are put in front of the participants and they are asked to get the small ball bounced back, up to that height from where it is put on the ground, to achieve the target. The paper states about five achievable methods (method 1-5), out of which the fifth method is the most appropriate. Also, it reveals that only 3 and 0.5 per cent of the respondents adopted the fourth and fifth method respectively, and those who implemented these methods, their performance in the work life is excellent. All these five methods demonstrate respondents' different traits. Through this simple-exercise, participants will be able to internalize their attitude, creativity, information seeking ability, listening and learning attitude, persuasion and problem-solving skills, etc. in class room. - Reproduced.
Keywords: Organizations; Problem solving